Thermal Microstructural Multiscale Simulation of Solidification and Eutectoid Transformation of Hypereutectic Gray Cast Iron - Urrutia, Alejandro; Celentano, Diego J.; Gunasegaram, Dayalan R.; Deeva, Natalia (Metallurgical and materials transactions. A, Physical metallurgy and materials science, 2014)
Although the gray cast iron solidification process has been the subject of several modeling studies, almost all available models appear to deal with only the more widely used hypoeutectic compositions. Models related to hypereutectic gray iron compositions with lamellar (or flake) graphite, and in particular for the proeutectic and eutectoid zones, are hard to find in the open literature. Hence, in the present work, a thermal microstructural multiscale model is proposed to describe the solidification and eutectoid transformation of a slightly hypereutectic composition leading to lamellar graphite gray iron morphology. The main predictions were: (a) temperature evolutions; (b) fractions of graphite, ferrite, and pearlite; (c) density; and (d) size of ferrite, pearlite, and gray eutectic grains; (e) average interlamellar graphite spacing; and (f) its thickness. The predicted cooling curves and fractions for castings with two different compositions and two different pouring temperatures were validated using experimental data. The differences between this model and existing models for hypoeutectic compositions are discussed.